The Right Data at the Right Time: How Tiered Access Is Changing Linked Data in Australia - Miller, Kate; Flack, Felicity (International Journal of Population Data Science, 2026)
For over 30 years, Australia has provided bespoke, record-level linked data to thousands of researchers — enabling significant health discoveries. But this approach is costly. The necessary governance means extensive application and approval processes, and data often fails to align with data-minimisation principles. The Population Health Research Network (PHRN), began hearing a consistent message. Important research wasn’t coming to fruition, was underpowered, or lacked critical data to answer research questions. Studies were failing — not because merit or team expertise, but because researchers were unable to assess feasibility in advance or receive the necessary data within the required timeframe. We have learnt that one size does not fit all. There was a clear need for timely, fit-for-purpose linked data — the right data at the right moment. This presentation introduces how the PHRN implemented tiered data offerings to meet researchers’ needs. Mock data allows rapid exploration of datasets and supports code development while waiting for real data; synthetic data allows hypothesis testing and modelling; and aggregate data provide sample size estimates for feasibility assessment. By providing only the data needed at each stage, the PHRN can respond quickly, improve efficiency, and better align with data-minimisation principles. Built on state-wide linked data and strong privacy protections, researchers can now access critical study-defining information and understand feasibility before a project begins. This presentation will outline how the PHRN redefined data provision through co-design activities and strengthened governance frameworks—demonstrating how a tiered access model is making linked data more responsive and accessible for Australian researchers.